Comparison of different methods of determination of total fluoride content in soil - WU Wei-hong; XIE Zheng-miao; XU Jian-ming; LIU Chao (浙江大学学报. 农业与生命科学版)
The standard curve method, TISAB standard additions method, and perchloric acid standard additions method were described for the determination of total fluoride in soil using fluoride ion-selective electrode. TISAB standard additions method gave highest average recovery of 96.8% (ranging 86.9%-102.3%) among three methods. The perchloric acid standard additions method and the standard curve method had the average recovery of 93.8% and 88.4%, respectively. It was found that there was no significant difference between the results obtained by three methods. Comparatively, the perchloric acid standard addition method was distinguished by its convenience, simplicity, and rapidity in total fluoride measurement.